Out of the Hat. - Burns, Simon (Far Eastern Economic Review, 2000)
An interview with Bob Young, the chairman and co-founder of Red Hat, a company that develops and distributes the Linux computer operating system. Topics discussed include how the company hopes to make money when other companies can copy their product and sell it for less; the revenue that Red Hat makes from services; the ways in which the company is building its brand; the challenge of competing with established companies such as Microsoft and IBM; Red Hat as the company that could overtake Microsoft in the operating-systems market; the prospect of Microsoft marketing its own version of Linux; means of adding value to Linux without adding unnecessary features to the software; how cultural differences between Asia and the U.S. affect Red Hat marketing strategy; and the progress that Red Hat has made in Asia.